Menstrual changes after COVID-19 vaccination and/or SARS-CoV-2 infection and their demographic, mood, and lifestyle determinants in Arab women of childbearing age, 2021 - Amer, Ahmed A.; Amer, Samar A.; Alrufaidi, Khaled Masoud; Abd-Elatif, Eman Elsayed; Alafandi, Bana Zuhair; Yousif, Dalia Abdelmonaim; Armi, Nadia Toukah; Alkhalaf, Atheer Abdulaziz; Shah, Jaffer; Ramadan, Mohamed Sh (Frontiers in Reproductive Health, 2022)
Background: By September 2, 2021, over 30,000 COVID-19-vaccinated females had reported menstrual changes to the MHRA's Yellow Card surveillance system. As a result, the National Institutes of Health (NIH) is urging researchers to investigate the COVID-19 vaccine's effects on menstruation. Therefore, this study was conducted to explore the menstrual changes after COVID-19 vaccination and/or SARS-CoV-2 infection and their interrelations with the demographic, mood, and lifestyle factors in Arab women of childbearing age (CBA). Methodology: A cross-sectional study was conducted during October 2021 using an Arabic validated and self-administrated questionnaire. In total, 1254 Women of (CBA).in the Arabic Population (15–50 y) with regular menstrual cycles were randomly selected from five countries (Saudi Arabia, Egypt, Syria, Libya, and Sudan). Results: The mean (SD) age of the 1254 studied females was 29.6 (8.5) years old. In total, 634 (50%) were married, 1104 (88.0%) had a university education or above, 1064 (84.4%) lived in urban areas, and 573 (45.7%) had normal body weight. Moreover, 524 (41.8%) were COVID-19 cases and 98 women (18.7%) reported menstrual changes (MCs). The 1044 (83.5%) vaccinated females reported 418 (38.5%) MCs after being vaccinated, and these MCs resolved in 194 women (55.1%) after more than nine months. Statistically significant relationships were observed between the reported MCs and the following variables: age, marital status, level of education, nationality, residence, and BMI. MCs were reported at 293(80.6) after the 2nd dose, and were mainly reported after 482 (46.1) Pfizer, 254 (24.3) Astrazenica, and 92 (8.8) Senopharm. Conclusion: MCs among women of CBA after COVID-19 infection and vaccination are a prevalent and complex problem, and had many determinates.